2021
DOI: 10.53941/tmep.v1i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Exercise with Energy Restriction as a Means of Losing Body Mass while Preserving Muscle Quality and Ameliorating Co-morbidities: Towards a Therapy for Obesity?

Abstract: Exercise with Energy Restriction as a Means of Losing Body Mass while Preserving Muscle Quality and Ameliorating Co-morbidities: Towards a Therapy for Obesity? Antonia Giacco1*, Elena Silvestri1*, Rosalba Senese2, Federica Cioffi1, Arianna Cuomo2, Assunta Lombardi3, Maria Moreno1, Antonia Lanni2 and Pieter de Lange()2  1Dipartimento di Science e Tecnologie, Università degli Studi del Sannio, Benevento, Italy 2Dipartimento di Scienze e Tecnologie Ambientali, Biologiche e Farmaceutiche, Università degli Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Weight loss by nutritional interventions often leads to muscle weakness [ 1 ]. In studies focusing on evaluating optimal weight-loss strategies, mild endurance exercise has emerged to be sufficient to counteract the negative impact of various energy-restricting nutritional interventions on muscle strength and quality in obese and non-obese subjects (see, for review, [ 1 ]), and in rodents alternate fasting and exercise has likewise been shown to improve endurance performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight loss by nutritional interventions often leads to muscle weakness [ 1 ]. In studies focusing on evaluating optimal weight-loss strategies, mild endurance exercise has emerged to be sufficient to counteract the negative impact of various energy-restricting nutritional interventions on muscle strength and quality in obese and non-obese subjects (see, for review, [ 1 ]), and in rodents alternate fasting and exercise has likewise been shown to improve endurance performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss by nutritional interventions often leads to muscle weakness [ 1 ]. In studies focusing on evaluating optimal weight-loss strategies, mild endurance exercise has emerged to be sufficient to counteract the negative impact of various energy-restricting nutritional interventions on muscle strength and quality in obese and non-obese subjects (see, for review, [ 1 ]), and in rodents alternate fasting and exercise has likewise been shown to improve endurance performance [ 2 ]. In this light, at the biochemical level there exists evidence for a compensatory role for exercise on fasting-mediated protein breakdown linked to insulin-independent reactivation of Akt/mammalian target of rapamycin (mTOR) C1 signaling in mice [ 3 ] and humans [ 4 ], which would impact muscle mass and quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with dietary interventions, exercise therapy helps to both prevent and mitigate the impact of MS. Chronic resistance and endurance exercise training, alone or in combination, reduce body weight, blood pressure, and improve lipid profiles, e.g., raising high-density lipoproteins (HDL) and lowering triglycerides [ 16 , 17 , 18 , 19 , 20 ]. The most beneficial effects of exercise training have been reported on IR [ 20 , 21 , 22 , 23 ].…”
mentioning
confidence: 99%